'Actually existing' right-wing populism in rural Europe: insights from eastern Germany, Spain, the United Kingdom and Ukraine. Issue 7 (9th November 2020) - Mamonova, Natalia; Franquesa, Jaume; Brooks, Sally
ABSTRACT: This study depicts various manifestations of what we call 'actually existing' right-wing populism. Based on empirical insights from eastern Germany, Spain, the UK and Ukraine, we explored how nationalist tendencies unfold in different contexts and what role agriculture and rural imageries play in this process. We analyse contextual factors (rural 'emptiness', socio-economic inequality, particularities of electoral systems, politics of Europeanization) and citizens' perceptions of social reality (selective memory, subjective experiences of democracy, national redefinition, politics of emotions). We conclude that resistance and alternatives to right-wing populism should be context-specific, grounded in the social fabric and culture of the locale.